Relationship of Plasma N‐terminal Pro‐brain Natriuretic Peptide Concentrations to Heart Failure Classification and Cause of Respiratory Distress in Dogs Using a 2nd Generation ELISA Assay. (10th October 2014) - Fox, P.R.; Oyama, M.A.; Hezzell, M.J.; Rush, J.E.; Nguyenba, T.P.; DeFrancesco, T.C.; Lehmkuhl, L.B.; Kellihan, H.B.; Bulmer, B.; Gordon, S.G.; Cunningham, S.M.; MacGregor, J.; et al.
<x xml:space="preserve">Abstract</x> Background Cardiac biomarkers provide objective data that augments clinical assessment of heart disease (HD). Hypothesis/Objectives Determine the utility of plasma N‐terminal pro‐brain natriuretic peptide concentration [NT‐proBNP] measured by a 2nd generation canine ELISA assay to discriminate cardiac from noncardiac respiratory distress and evaluate HD severity. Animals Client‐owned dogs (n = 291). Methods Multicenter, cross‐sectional, prospective investigation. Medical history, physical examination, echocardiography, and thoracic radiography classified 113 asymptomatic dogs (group 1, n = 39 without HD; group 2, n = 74 with HD), and 178 with respiratory distress (group 3, n = 104 respiratory disease, either with or without concurrent HD; group 4, n = 74 with congestive heart failure [CHF]). HD severity was graded using International Small Animal Cardiac Health Council (ISACHC) and ACVIM Consensus (ACVIM‐HD) schemes without knowledge of [NT‐proBNP] results. Receiver‐operating characteristic curve analysis assessed the capacity of [NT‐proBNP] to discriminate between dogs with cardiac and noncardiac respiratory distress. Multivariate general linear models containing key clinical variables tested associations between [NT‐proBNP] and HD severity. Results Plasma [NT‐proBNP] (median; IQR) was higher in CHF dogs (5, 110; 2, 769–8, 466 pmol/L) compared to those with noncardiac respiratory distress (1, 287; 672–2, 704 pmol/L; P < .0001). A cut‐off >2, 447 pmol/L discriminated CHF from noncardiac respiratory distress (81.1% sensitivity; 73.1% specificity; area under curve, 0.84). A multivariate model comprising left atrial to aortic ratio, heart rate, left ventricular diameter, end‐systole, and ACVIM‐HD scheme most accurately associated average plasma [NT‐proBNP] with HD severity. Conclusions and Clinical Importance Plasma [NT‐proBNP] was useful for discriminating CHF from noncardiac respiratory distress. Average plasma [NT‐BNP] increased significantly as a function of HD severity using the ACVIM‐HD classification scheme.